Determination of Subsurface Structure of Landslide Area According to Interpretation of Resistivity Data - Supeno Supeno; Nurul Priyantari; Gusfan Halik (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
Resistivity method is a useful geophysical tool for investigating landslides. It can be used to estimate the subsurface structure of a landslide mass, the depth of the failure surface, and the lateral extent of a landslide. High resolution of resistivity data were obtained by applying Schlumberger configuration, while penetrating deepness was obtained by applying Vertical Electrical Sounding (VES) configuration. Interpretation of subsurface condition showed there was soil layer in survey area which was indicated as slip surface triggering the landslide.